The answer is: Substitution property of equality.
The explanation is shown below:
1. To solve this problem you must apply the proccedure shown below:
2. When you clear the variable x from the first equation, and subtitute it into the second equation, you obtain:
<span>3x−2y=10
x=(10+2y)/3
4x−3y=14
</span>4[(10+2y)/]−3y=14
<span> y=-2
3. When you subsitute y=-2 into the first equation and clear the x, you have:
x=2
</span>
Cut 5 equal sections from a 2 foot long ribbond
What was the recipe? 1 1/8 is only one measurement and this question requires 2.
f(x)=x-4f(3)=3-4so f(3)= -1
Answer:330
Step-by-step explanation:
15*22=330